Content validity of the Brief and Comprehensive ICF Core Sets for common disabling conditions in a developing country. Issue 2 (June 2021) - Pathak, Anupa; Abbott, Haxby J; Sharma, Saurab; Ribeiro, Daniel Cury; Heinemann, Allen W.
Abstract : Supplemental Digital Content is available in the text. Abstract : The International Classification of Functioning, Disability and Health (ICF) features associated tools, the Brief and Comprehensive ICF Core Sets. These are designed to be universally applicable, but have limited evidence of content validity (i.e. comprehensiveness and relevance) in low income, non-Western countries. In this cross-sectional study, we aimed to assess the content validity of the ICF Core Sets in Nepal. We interviewed 161 participants with stroke, spinal cord injury (SCI), chronic obstructive pulmonary disease (COPD), and musculoskeletal conditions and asked them to identify activities they had difficulty performing due to their health condition. We mapped 544 participant responses to the ICF and assessed if these ICF categories were represented in the respective ICF core sets. The Comprehensive Core Sets for stroke, COPD, SCI, and musculoskeletal conditions contained more items identified by participants than the respective Brief Core Sets (e.g., 89% vs. 26% in stroke). Among ICF categories that represented at least 5% of participants' responses, the Brief Core Sets covered 40%–71% of participants' responses whereas the Comprehensive Core Sets covered 67%–100% of responses. This is the first study to evaluate the content validity of the ICF Brief and Comprehensive core sets in Nepali individuals with stroke, SCI, MSK conditions, and COPD. The Comprehensive Core Sets for stroke, COPD, and SCI have adequate content validity for use in clinical practice and research in Nepal; the Brief Core Sets may not adequately meet local and individual needs unless supplemented with additional ICF categories.